“Malin Kundang, Ibunya Durhaka”: Suatu Pendekatan Genetik - Ronidin _ (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2013)
This paper discusses the influence of kaba “Malin Kundang" as a form of oral literature of the shortstory parody Minangkabau A.A. Navis entitled "Malin Kundang, Ibunya Durhaka" (“MKID”). Thediscussion carried out by using a genetic approach. Genetic approach examines how the work affectsthe work of others. Analysis conducted “MKID” illustrates that the short story as a parody of theaffected works of kaba "Malin Kundang" indicates a social critique of Navis toward modern society—especially the people within the scope of the author, the Minangkabau people—whom have beenuprooted from its cultural roots, so that in everyday life they become materialistic and overturning ofmoral values and religion. In pursuit of his passion, they perform a variety of "sedition" is sometimeshard to accept common sense. World upside down in a short story in which a “MKID” mother"disobey" her and "cheating" for his worldly needs, is a portrait of a sick society, unstable, and turnedupside down.